Thirty Years in the Design and Development of Cruzain Inhibitors - Jasinski, Gabriel Jorge (2024)
Cruzipain is the principal protease of Trypanosoma cruzi, the etiological agent of Chagas disease. Since its discovery in the 1980s and the resolution of the crystal structure of cruzain (a truncated recombinant form of the enzyme) in 1995, this target has attracted the interest of many research groups for screening studies, structure-based and ligand-based drug design campaigns, which include peptide-like and non-peptide synthetic compounds. In this context, empirical and computational methods have proven to be valuable tools for the study of mechanisms of action, potential binding modes and structure-activity relationships for a diverse series of cruzain/cruzipain inhibitors. This paper, therefore, reviews some of the most relevant chemical groups reported as cruzain inhibitors over the last 30 years of research.